(untitled) - Davis, Mackenziel Leo (New York, NY, 2004)
Principles of Environmental Engineering and Science by Mackenzie Davis and Susan Masten is intended for a course in introductory environmental engineering for sophomore- or junior-level students. The emphasis of this new text is on engineering principles rather than on engineering design. The concept of mass balance is carried throughout the text as a tool for problem solving, and the text boasts extensive coverage of chemistry, biology, and hydrology than other books have. The chemistry review in Chapter 2 and coverage of ethics will aid students in better understanding the engineering topics presented in the book
Keywords: Environmental engineering,Environmental sciences